2007
DOI: 10.1108/02635570710816694
|View full text |Cite
|
Sign up to set email alerts
|

The role of joint collaboration planning actions in a demand‐driven supply chain

Abstract: PurposeDrawing on the operations and information systems literature as well as concepts tied to buyer‐seller relationships, the objective of this exploratory research is to measure the influence of joint collaboration planning actions on the strength of relationships, interorganizational information systems (IOISs) use and firm flexibility. The path model proposed in this study also posits that joint collaboration planning actions and the strength of relationships positively affect IOISs use, which in turn pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 109 publications
6
89
0
2
Order By: Relevance
“…(i) ações conjuntas: é no nível tático que equipes atuam no desenvolvimento de projetos conjuntos na área logística, no planejamento conjunto de operações e outras ações em parceria que podem ocorrer com as áreas funcionais das empresas envolvidas (Hadaya & Cassivi, 2007);…”
Section: Elementos De Integração Táticaunclassified
See 1 more Smart Citation
“…(i) ações conjuntas: é no nível tático que equipes atuam no desenvolvimento de projetos conjuntos na área logística, no planejamento conjunto de operações e outras ações em parceria que podem ocorrer com as áreas funcionais das empresas envolvidas (Hadaya & Cassivi, 2007);…”
Section: Elementos De Integração Táticaunclassified
“…Fawcett et al (2008), Hadaya & Cassivi (2007), Danese (2007), Lee et al (2007), Matopoulos et al (2007), Maylett & Vitasek (2007), Sandberg (2007), Whipple & Russell (2007), Vereecke & Muylle (2006), Fu & Piplani (2004).…”
mentioning
confidence: 99%
“…The different types of connection can influence the type of information, the mechanisms of performance control, and the forms of production management, among various other aspects. Several studies have found that more cooperative relations among companies in the chain lead to gains (GHOSH & FEDOROWICZ, 2008;SOOSAY, HYLAND & FERRER, 2008;HADAYA & CASSIVI, 2007). Supplier relations management is a central process in the model of Lambert et al (1998).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Introducing an electronic exchange platform not only involves technical innovations but also considerable environmental and organizational changes, including changes in interorganizational relationships, the beliefs and attitudes of senior executives, managerial styles, and shared values. Joining an electronic exchange platform effort strengthens the relationships between supply chain companies 13 and companies that have bargaining power over key suppliers. Collaboration and long-term relationships are also more probable in an electronic exchange platform 14 .…”
Section: Increased Electronic Cooperative Relationshipsmentioning
confidence: 99%